The development of multidimensional poverty in Germany 1985 - 2007 - Christopher Busch; Andreas Peichl (Institute for the Study of Labor (IZA), 2010)
This paper deals with concepts of multidimensional poverty measurement and applies them to Germany. Three concepts of poverty are examined and included into one multidimensional approach: economic well being, capability and social exclusion. The empirical application relies on indices introduced by Bourguigon and Chakravarty (2003), and Alkire and Foster (2008). It uses data from the German Socio-Economic Panel study. The indices are tested for their robustness in several aspects, and the influence of changing levels of substitutability between achievements on the poverty dimensions is examined. It transpires that the depth of poverty is relatively stable for the period 1985 to 2007. A structural analysis of the poor in 2007 reveals that the group at greatest risk of poverty is the unemployed.
Keywords: I00; I32; O15; D63; 330; Multidimensional measurement; poverty; deprivation; inequality; Armut; Lebensstandard; Disparitätsmaß; Soziale Isolation; Arbeitslosigkeit; Deutschland